Analisis Dinamis Pengaruh Produksi, Harga dan Konsumsi terhadap Volume Ekspor Crude Palm Oil (CPO) di Indonesia Menggunakan Pendekatan Vector Error Correction Model - Sari, Yolanda; Safitri, Tharisa; Amali, Muhammad (Universitas Batanghari Jambi, 2025)
This study aims to determine and analyze the development of CPO production, prices, consumption, and export volume in Indonesia. The data used in this study were obtained from the Central Statistics Agency (BPS), the Indonesian Palm Oil Association (GAPKI), and the World Bank for the period 2003-2023. The results of data analysis using the Vector Error Correction Model (VECM) indicate that CPO production and price variables have a positive and significant influence on CPO export volume in both the short and long term. Meanwhile, CPO consumption only has a positive and significant effect in the short term, but does not show a significant effect in the long term.